Strategi Inovatif dan Efektif untuk Meningkatkan Kemampuan Membaca Cepat Peserta Didik di Era Pembelajaran Modern (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Speed reading is an essential skill in modern education, requiring students to quickly and effectively comprehend information. This study aims to examine innovative and effective strategies for developing students' speed reading abilities in the era of modern learning. The research method used is library research, involving an extensive review of books, scholarly journals, and previous studies relevant to speed reading instruction. The findings indicate that the most effective strategies for improving speed reading skills include a combination of skimming and scanning techniques, minimizing subvocalization, and practicing word visualization. Additionally, the integration of digital technologies, such as AI-based learning applications and interactive platforms, has been shown to enhance both reading speed and comprehension. Constructivist and cognitive learning theories also play a crucial role in developing adaptive strategies tailored to students' needs. Despite the proven effectiveness of these strategies, several challenges remain, such as low reading motivation, difficulties in maintaining focus, and limited access to technology in certain educational settings. Therefore, educators must foster a conducive learning environment and incorporate appropriate technological tools to support the development of speed reading skills. This study contributes to the development of more innovative and adaptive speed reading instructional models in the digital era. The findings are expected to serve as a reference for educators in implementing more effective strategies to enhance students' speed reading abilities.